2009
DOI: 10.1177/1091581809340331
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Signaling in Neuronal Cells Exposed to the Munitions Compound Cyclotrimethylenetrinitramine (RDX)

Abstract: Cyclotrimethylenetrinitramine (RDX) has been used extensively as an explosive in military munitions. Mechanisms for seizure production, seen in past animal studies, have not been described. Increased calcium levels contribute to excitotoxicity, so in this study neuroblastoma cells are loaded with calcium-indicating dye before application of 1.5 microM to 7.5 mM RDX, with fluorescence recorded for 30 cycles of 11 seconds each. The lowest concentration of RDX increases calcium fluorescence significantly above ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 22 publications
(40 reference statements)
0
1
0
Order By: Relevance
“…Many studies have observed these seizures [21,22], though there has been little work carried out on their neurological or mechanistic basis. In vitro studies suggested that RDX may affect calcium signaling in neurons [34], but in vivo, RDX-induced seizures were not blocked by verapramil, a potent calcium channel blocker [35]. They have been observed in humans [23][24][25], pigs [26,27], dogs [22], rodents [28][29][30], and birds [31][32][33]; the no observed adverse effect level (NOAEL) is consistent across taxonomic groups.…”
Section: Mammalian Toxicitymentioning
confidence: 99%
“…Many studies have observed these seizures [21,22], though there has been little work carried out on their neurological or mechanistic basis. In vitro studies suggested that RDX may affect calcium signaling in neurons [34], but in vivo, RDX-induced seizures were not blocked by verapramil, a potent calcium channel blocker [35]. They have been observed in humans [23][24][25], pigs [26,27], dogs [22], rodents [28][29][30], and birds [31][32][33]; the no observed adverse effect level (NOAEL) is consistent across taxonomic groups.…”
Section: Mammalian Toxicitymentioning
confidence: 99%